(untitled) - Welling, Bruce (Markham, 2010)
Canadian corporate law: Cases, notes & materials maintains its primary purpose of providing an accessible and authoritative casebook for the teaching of general or survey courses in business associantions/organizations or corporate law in any jurisdiction in Canada.
Keywords: Corporation law,Luật doanh nghiệp; Canada,Canada